-2(a+3)-a=0

Simple and best practice solution for -2(a+3)-a=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(a+3)-a=0 equation:


Simplifying
-2(a + 3) + -1a = 0

Reorder the terms:
-2(3 + a) + -1a = 0
(3 * -2 + a * -2) + -1a = 0
(-6 + -2a) + -1a = 0

Combine like terms: -2a + -1a = -3a
-6 + -3a = 0

Solving
-6 + -3a = 0

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '6' to each side of the equation.
-6 + 6 + -3a = 0 + 6

Combine like terms: -6 + 6 = 0
0 + -3a = 0 + 6
-3a = 0 + 6

Combine like terms: 0 + 6 = 6
-3a = 6

Divide each side by '-3'.
a = -2

Simplifying
a = -2

See similar equations:

| -2.5c+6.7=-1.3 | | 15=5x+5 | | -7.1+5w=5.4 | | 18x^2+33x-15=6 | | 12-3t=6 | | 3+5n=18 | | -20=-2t-4 | | 2n+n+1=7 | | (4n+5)(n-6)=0 | | 7=6(2z+3)-5 | | -36=-9t | | -5x+14.7=2.2 | | -4=t | | (w-10)+64=98 | | 11=2-3y | | 6x^2-11x=-3 | | 3n+7=-23 | | 7=6(1-2y)-5 | | 7x^2-23x+6=0 | | 6.1=-1.4+3v | | 4s=45.5 | | -6(7k+11)=24 | | 6.1=-14+3v | | 2(3n+2)=.5(-3n+2) | | 2*(a+5)= | | 3(-3)+2=11 | | (2*a)+5= | | 16x^2+16x-5=0 | | b+b+112=524 | | -(-2-n)= | | 8w+4=36 | | 2(.6666667x)+2(x)=96 |

Equations solver categories